High-Resolution Alma Observations of v4046 Sgr: A Circumbinary Disc with a Thin Ring - Carcamo-Vasquez, M; Perez-Marquez, S; Weber, P (Oxford University Press, 2022)
The nearby V4046 Sgr spectroscopic binary hosts a gas-rich disc known for its wide cavity and dusty ring. We present high resolution (∼20 mas or 1.4 au) ALMA observations of the 1.3 mm continuum of V4046 Sgr which, combined with SPHERE-IRDIS polarised images and a well-sampled spectral energy distribution (SED), allow us to propose a physical model using radiative transfer predictions. The ALMA data reveal a thin ring at a radius of 13.15 ± 0.42 au (Ring13), with a radial width of 2.46 ± 0.56 au. Ring13 is surrounded by a ∼10 au-wide gap, and it is flanked by a mm-bright outer ring (Ring24) with a sharp inner edge at 24 au. Between 25 and ∼35 au the brightness of Ring24 is relatively flat and then breaks into a steep tail that reaches out to ∼60 au. In addition, central emission is detected close to the star which we interpret as a tight circumbinary ring made of dust grains with a lower size limit of 0.8 mm at 1.1 au. In order to reproduce the SED, the model also requires an inner ring at ∼5 au (Ring5) composed mainly of small dust grains, hiding under the IRDIS coronagraph, and surrounding the inner circumbinary disc. The surprisingly thin Ring13 is nonetheless roughly 10 times wider than its expected vertical extent. The strong near-far disc asymmetry at 1.65 rm{mu m} points at a very forward-scattering phase function, and requires grain radii of no less than 0.4 rm{mu m}. © 2021 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.